2007
DOI: 10.1097/bcr.0b013e318093e4ca
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Function

Abstract: Restoration of function is crucial to the performance of activities of daily living, vocational and recreational activities, as well as to community integration and psychosocial aptitude. Strategies to optimize restoration of function include both physical considerations as well as metabolic considerations that can significantly impact physical capacity. Given the breadth of this topic, Drs. Herndon and deLateur focused on two of the most critical facets of restoration of function: metabolic support of the bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Initially, it was thought that these derangements would subside shortly after the acute hospitalization or the initial resuscitation. More recent research has shown that these responses may last 9–12 months after the initial insult [16], [73], [74]. Here, we demonstrated a significant increase in cardiac work up to three years after the initial injury.…”
Section: Discussionsupporting
confidence: 64%
“…Initially, it was thought that these derangements would subside shortly after the acute hospitalization or the initial resuscitation. More recent research has shown that these responses may last 9–12 months after the initial insult [16], [73], [74]. Here, we demonstrated a significant increase in cardiac work up to three years after the initial injury.…”
Section: Discussionsupporting
confidence: 64%
“…29,30 Some studies investigate the impact of exercise on functional outcome as well. [31][32][33] However, to the best of our knowledge, there are few randomized controlled studies (pediatric or adult) that examine the effects of exercise on ROM. In 2003, Celis et al 34 randomized 53 pediatric patients to either a 12-week hospital-based exercise program or a 12-week homebased physical rehabilitation program without exercise.…”
Section: Discussionmentioning
confidence: 96%
“…For example, years following a burn injury, fatigue is an “almost universal complaint” as a major barrier preventing such individuals from returning to work and performing activities of daily living. 20 59% of burned individuals report problems with fatigue an average of 17 years post-injury. 21 Other perceived or real barriers to physical activity may include impaired temperature regulation, hypertrophic scars and contractures that may limit range of motion, hyperpigmentation, psychosocial barriers, decreased cutaneous sensation, and a lower quality of life.…”
Section: Discussionmentioning
confidence: 99%